Teaching Gradually Practical Pedagogy for Graduate Students, by Graduate Students. - Armstrong, Kacie L. (Stylus Publishing, LLC, 2021)
There's an epidemic of leadership failure--whether something as small as a meeting, or as large as implementing enterprise wide change. Leaders know that sinking feeling when a gap emerges between themselves and the groups they most need to engage with. Leaders and business schools are looking in the wrong places for the cause. What holds most leaders back, as if their foot is always on the brake, is their failure to engage, and gain alignment. This book shows the reasons why. Leaders rarely recognise that: Shaping group behavior is describable as a process, which they can learn. Instead, they unconsciously fall into relationship patterns influenced by early family experiences. Informal relationship patterns have a dramatic effect on results, which is why birds in flight manage to alter course without bumping into each other. Leadership and collaboration are primarily a matter of principles and process, and not personality and content alone. If leaders master the process, they achieve consistent results. This book reveals the leadership levers to release the power of relationships for exceptional participation, alignment and results in organizations. It enables leaders to mine the brilliance that often lies dormant and untapped within their organizations. Readers will have the principles and tools to go beyond the agenda, truly engage with those around them, and release untapped capacities within their organizations. These qualities and skills will inspire associates and employees.